Atlas des fossiles caractéristiques du Lias portugais* III a) Domérien (Ammonites) - Mouterde, R. (2011)
This fascicle, dedicated to the Domerian (Late Pliensbachian) ammonites faunas, is the third part of the “Atlas des fossiles caractéristiques du Lias portugais“. It follows two previous publications about the Hettangian-Sinemurian and the Carixian (Lower fifty species are concisely described and illustrated. The other groups (nautilids, belemnites, brachiopods, bivalvia...) will be published afterwards. The principal objective of the “Atlas des fossiles caractéristiques du Lias portugais“ is to make the main liassic lusitanian fossils known to a wide public. It also aims to support field studies by giving a rich iconography dedicated to the lusitanian invertebrate macrofaunas. In the case of the ammonites, all the species are described and the “Atlas” can be used as an exhaustive database for biostratigraphic and paleobiogeographic studies.